Adolescent Development in Context: A Decade Review of Neighborhood and Activity Space Research. (24th November 2021) - White, Rebecca M. B.; Witherspoon, Dawn P.; Wei, Wei; Zhao, Chang; Pasco, Michelle C.; Maereg, Tiyobista M.
Abstract : Over the last decade, two lines of inquiry have emerged from earlier investigations of adolescent neighborhood effects. First, researchers began incorporating space‐time geography to study adolescent development within activity spaces or routine activity locations and settings. Second, cultural‐developmental researchers implicated neighborhood settings in cultural development, to capture neighborhood effects on competencies and processes that are salient or normative for minoritized youth. We review the decade's studies on adolescent externalizing, internalizing, academic achievement, health, and cultural development within neighborhoods and activity spaces. We offer recommendations supporting decompartmentalization of cultural‐developmental and activity space scholarship to advance the science of adolescent development in context.